Analysis on the free swell index of plastic soils in Metro Manila - Agustin, Aljohn T.; Sy, Denniel Steven T.
Expansive soils undergo significant volume changes with an increase in moisture. The shrink-swell mechanism causes cracks and minor damages to structures such as pavements, foundations and on-grade slabs. An alternative method is used in assessing the soil expansivity through the Free Swell Index Test (IS 2720) which is practical and easier to conduct as compared to the oedometer test. The study aims to verify the repeatability of the free swell index test as a reliable method for soil expansivity characterization and to generate a map of free swell indices in Metro Manila. A total of 61 samples was obtained using Systematic Random Sampling with Clustering (SyRSCS). Using the plasticity index as a criterion, 29 soils samples have Pls greater than or equal to 15 and were tested for expansivity. Five soils are low in expansivity, three soils have medium expansivity, seven are highly expansive and fourteen are very high in expansivity. The FSI test was done in thirty trials for the repeatability test. The repeatability and reproducibility standard deviations are 5.47291 and 6.19462, respectively. Furthermore, the repeatability and reproducibility limits are 15.32414 and 17.34495. To describe the spatial variability of the FSI in Metro Manila using the 61 datapoints, five interpolation methods were used to create the output maps with a resolution of 100m: IDW, LPI, RBF, OK, and EBK. Conventional validation was used to determine the assessment indices and the results showed that the RBF and OK are the best interpolation methods. They performed the best in terms of interrater reliability in both the kappa statistic and the user's and producer's accuracies. In addition, the output maps were validated qualitatively, and it showed that the output maps agree with the available literature and personal communications.